Interaction between the state and civil society institutions in the Republic of Kazakhstan (Journal of actual problems of jurisprudence, 2019)
The development of civil society in the Republic of Kazakhstan and the availability of the Constitution, itis necessary to build a legal, democratic state. The media are an indispensable element of a developed civilsociety. The role of the civil institution of the information does not occur immediately and brought to theforefront by. In fact, it is the power of public opinion, it is an ancient institution of public discussion of theproblem at a meeting on the rhetorical contest. Modern technology makes the process more perfect.Keywords: Constitution, democracy, society, law, information.